Efektivitas Edukasi dalam Meningkatkan Pengetahuan dan Sikap Remaja tentang Vaksinasi HPV di SMKN 1 Bandung Tulungagung - Anissa Ariyati; Indra Yuliati; Reny I’tishom; Ratna Dwi Jayanti (Yayasan Jompa Research and Development, 2026)
ervical cancer is one of the leading causes of death among women worldwide, including in Indonesia. WHO data (2024) indicate that the incidence and mortality rates of cervical cancer remain high, mainly due to low levels of knowledge and awareness regarding prevention through HPV vaccination and early screening. Adolescent girls are a strategic group who should receive early education to foster understanding and positive attitudes toward cervical cancer prevention. This study aimed to analyze the effect of HPV vaccine education and the benefits of screening on the knowledge and attitudes of female adolescents at SMKN 1 Bandung Tulungagung. This research employed a quantitative approach with a pre-test and post-test design. The population consisted of all 10th-grade female students, with a total sample of 112 respondents selected based on inclusion criteria. The research instrument was a validated and reliable questionnaire measuring knowledge and attitudes. The intervention was carried out through educational sessions using presentation media and question-and-answer discussions. Data were analyzed using the Wilcoxon test with a significance level of α = 0.05. The results showed a significant improvement in both knowledge and attitudes after the educational intervention. The percentage of good knowledge increased from 59% to 94.6%, while positive attitudes rose from 89% to 94.6%. Statistical tests indicated p < 0.05 for both variables, confirming a significant effect of education on improving the knowledge and attitudes of female adolescents regarding cervical cancer prevention. These findings highlight that health education about the HPV vaccine and the benefits of screening is effective in enhancing adolescents’ awareness of the importance of early cervical cancer prevention. Keywords: Education, HPV vaccine, screening, knowledge, attitude